Nota técnica 2: A simple search model applied to R&D - Vatter, Jaime (Estudios de Economía, 2016)
There are several papers that use the simple search paradigm to analyze R&D investment. Here the firm invests a fixed amount each period, at the end of which, the value of the innovation is determined. Having this information available, the firm decides whether to stop the R&D project or not, i.e., to accept or reject what that period offers. The purpose of this note is to describe the simple search model in the R&D cases, as well as to elaborate on some of the implications of the model. It is of particular interest to compare two frameworks for subsidie